The Soils of Ireland (World Soils Book Series,, 2018)
This book provides a comprehensive overview of pedology in Ireland. It describes the main soil types of the country, their functions, ecological use, and the conditions to which they were subjected associated with management over time. In addition, it presents a complete set of data, pictures and maps, including benchmark profiles. Factors involved in soil formation are also discussed, making use of new, unpublished data and elaborations. The book was produced with the support and sponsorship of Teagasc, The Agriculture and Food Development Authority, Ireland and the Irish Environmental Protection Agency.